FAKTOR YANG MEMPENGARUHI KEAKURATAN DATA SENSUS HARIAN RAWAT INAP DI RSUD DR. R SOEDARSONO PASURUAN: Factors Affecting the Accuracy of Daily Inpatient Census Data at RSUD dr. R Soedarsono Pasuruan - Prisusanti, Retno Dewi; Hamzah, Ghufron Nur; Azkiya, Deva Zahrotul (Forind Press, 2024)
The process of operational planning and hospital decision making is assisted by the SIMRS system. Based on a preliminary survey conducted in the Medical Records section of RSUD doctors, R. Soedarsono found 400 SIMRS patient data and 300 manual patient data. Because staff members enter the same patient data multiple times, some of this data is duplicated. Information collected daily from short-term and inpatients is used for ongoing screening considerations from day to day, week to week, and month to month. The aim of this research is to find out what influences the accuracy of SIMRS daily inpatient census data. A quantitative approach with descriptive methods was used for this research. The subject of the examination was a medical records officer, while the object of exploration was a PC gadget. The results of the examination showed a variety of officers' information regarding using SIMRS: 20% inadequate, 40% adequate, and 40% good. The SIMRS strategy was seen as half inappropriate and half inappropriate, while the hardware was 60% complete and 40% short. Medical record officers should receive training on how to calculate daily inpatient census data correctly.